2016
DOI: 10.1186/s40543-016-0085-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of three digestion methods for elemental analysis in traditional medicine products using atomic absorption spectrometry

Abstract: Background: Traditional medicine mainly of herbal origin is widely used all around the world. Heavy metal contamination in such products is frequently reported. Accumulation of heavy metals in the human body leads to various health hazards. Thus, precise determination for such contaminants is required for safety assurance. Sample preparation is a significant step in spectroscopic analysis to achieve reliable and accurate results. Wet digestion methods are basically used for the dissolution of herbal product sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(83 citation statements)
references
References 13 publications
0
63
0
3
Order By: Relevance
“…The data showed that, concentration (mg/kg) of copper in sediments ranged from 0.61 -3.19 with mean value of 1.56±1. 16. The highest concentration of copper was recorded at SS3 (3.19mg/kg), followed by SS1 (0.87mg/kg) and closely followed by SS2 (0.61mg/kg).…”
Section: Characteristics Of Surficial Sediment Qualitymentioning
confidence: 86%
See 1 more Smart Citation
“…The data showed that, concentration (mg/kg) of copper in sediments ranged from 0.61 -3.19 with mean value of 1.56±1. 16. The highest concentration of copper was recorded at SS3 (3.19mg/kg), followed by SS1 (0.87mg/kg) and closely followed by SS2 (0.61mg/kg).…”
Section: Characteristics Of Surficial Sediment Qualitymentioning
confidence: 86%
“…After cooling, 2.5 mL of 70 % HClO4 was added, and the mixture was gently boiled until dense white fumes appeared. Later, the mixture was allowed to cool, and 10 mL of deionized water was added followed by further boiling until the fumes were totally released according to standard method by [15,16].…”
Section: Sampling and Analysismentioning
confidence: 99%
“…One gram of dried material was digested with 12 ml of HCl: HNO 3 (1:3) to remove all organic matter from the plant samples. After digestion, the residue was washed with distilled water and filtered into a 50-ml volumetric flask and topped to the mark to await further analysis using an FAAS (Kumari, Parida, Rangani, & Panda, 2017;Thangaraj, 2016;Uddin et al, 2016;Yami, Chandravanshi, Wondimu, & Abuye, 2016).…”
Section: Estimation Of Macro-and Micronutrient Contentmentioning
confidence: 99%
“…The plants, top soil, and FW compost samples were acid digested using procedures described by Uddin et al (2016). Specifically, the samples were digested using a mixture of concentrated HNO 3 and HCl (ratio of 1:3).…”
Section: Measurement Of Plant Growth and Analysis Of Heavy Metal Uptakementioning
confidence: 99%